The Plant-Derived Chalcone 2, 2′, 5′-Trihydroxychalcone Provides Neuroprotection against Toll-Like Receptor 4 Triggered Inflammation in Microglia. (21st December 2015) - Jiwrajka, Manasi; Phillips, Alexandra; Butler, Matt; Rossi, Miriam; Pocock, Jennifer M.
Abstract : Chalcones are plant metabolites with potential for therapeutic exploitation as antioxidant, anti-inflammatory, and antiproliferative agents. Here we explored the neuroprotective effects of 2, 2′, 5′-trihydroxychalcone (225THC), a potent antioxidant with radical-scavenging properties. 225THC was found to be a potent inhibitor of apoptosis in stimulated primary rat neuronal cultures. This was likely mediated by an anti-inflammatory effect on microglial cells since 225THC inhibited LPS-stimulated TNF- α and IL-6 secretion from primary rat microglia and modulated the cytokine/chemokine profile of BV2 microglial cells. Additionally, 225THC inhibited LPS-evoked inducible nitric oxide synthase expression but did not influence endogenous superoxide generation. Microglial flow cytometric analyses indicated the 225THC treatment induced a shift from an M1-like phenotype to a more downregulated microglial profile. Taken together these data suggest that the chalcone 2, 2′, 5′-trihydroxychalcone can modulate neuroinflammatory activation in brain-derived microglia and holds promise as a therapeutic in neuroinflammatory conditions.